CHARACTERIZATION OF Pongamia pinnata L.Pierre. A REVIEW - Rout, S.; Beura, S.; Nayak, S.; Patra, S.S. (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2015)
Pongamia pinnata L.Pierre belongs to Leguminaceae family is underutilized tree. It’s traditionally used as illuminating oil and for lubrication and as curing medicine. In the present study Pongamia pinnata was studied for its multipurpose uses as watershed afforestation, avenue plantation and ethnomedicinal information. Overall, this paper gives an overview on covering the biology, and various industrial uses.